Natural Coloring Process Tie-Dye Tritik Combination Smock Technique In Children's Clothing Making - Ariyana Damayanti; Palung R L K N Sirah (An International Journal Tourism and Community Review, 2024)
Coloring is a technique of transferring color on a medium, either fabric, paper, as well as other objects that can absorb color. The coloring of the Japanese smock technique and the tie-dye technique, if they are combined in a fabric coloring process will produce new technology in the field of textiles that produce new pattern designs that are creative and innovative. The purpose of this study is: To find out the natural coloring process of the tie-dye tritik combination smock technique in the children's clothing making. The methods used in this coloring process are: 1) Research and Development Method; 2) Data Analysis. The process of making this natural coloring requires 4 trials using 2 types of natural colors with the help of a Validator as an assessor of the results of smock technique. The type of smock used is a Japanese smock pattern and the color chosen in this process is a material that is easy to get and is widely found around the author's environment. After determining the pattern and color used, continued by preparing tools and materials, selecting color materials, making color, making children's clothing. The conclusion that can be taken in the dyeing technique of this smock technique uses a good color locking material, one of which is alum, which has the property of binding color to the fabric.